Предмет: Математика,
автор: T90Ruslan2002
x-4/4-2=х/2
Ответы
Автор ответа:
0
(х-4)/4-2х-4/4--2=х/2
(х-4)/4-2х-1-2=х/2
(х-4)/4-2х-3=х/2 домножим на 4
4(х-4)/4-4*2х-4*3=4*х/2
х-4-8х-12=2х
-7х-16=2х
-7х-2х=16
-9х=16
х=- 16/9=-1 5/9
Но что-то мне подсказывает, что Вы условия не правильно записали
(х-4)/4-2х-1-2=х/2
(х-4)/4-2х-3=х/2 домножим на 4
4(х-4)/4-4*2х-4*3=4*х/2
х-4-8х-12=2х
-7х-16=2х
-7х-2х=16
-9х=16
х=- 16/9=-1 5/9
Но что-то мне подсказывает, что Вы условия не правильно записали
Похожие вопросы
Предмет: Қазақ тiлi,
автор: azamm77
Предмет: Русский язык,
автор: advrfihweo7g
Предмет: Русский язык,
автор: Drakon0601
Предмет: Физика,
автор: NataliaOr
Предмет: Алгебра,
автор: lordrauhl